This action might not be possible to undo. Are you sure you want to continue?

BooksAudiobooksComicsSheet Music### Categories

### Categories

### Categories

Editors' Picks Books

Hand-picked favorites from

our editors

our editors

Editors' Picks Audiobooks

Hand-picked favorites from

our editors

our editors

Editors' Picks Comics

Hand-picked favorites from

our editors

our editors

Editors' Picks Sheet Music

Hand-picked favorites from

our editors

our editors

Top Books

What's trending, bestsellers,

award-winners & more

award-winners & more

Top Audiobooks

What's trending, bestsellers,

award-winners & more

award-winners & more

Top Comics

What's trending, bestsellers,

award-winners & more

award-winners & more

Top Sheet Music

What's trending, bestsellers,

award-winners & more

award-winners & more

Welcome to Scribd! Start your free trial and access books, documents and more.Find out more

Taylor and Maclaurin Series:

Monday, April 4

As a reminder we now have Taylor polynomials, power series and in the Motivation section (even though we didn’t know what a series was at that time) we gave ”inﬁnite degree” Taylor polynomials. In this section we hope to make sense out of those ”inﬁnite degree” polynomials. We begin by assuming that we have a function f (x) that has is equal to a power series expansion, say around x = a:

∞

f (x) =

n=0

an (x − a)n = a0 + a1 (x − a) + a2 (x − a)2 + a3 (x − a)3 + · · ·

(1)

The example of such a function and power series that you might use as a model is the function and series (expanded around x = 0) 1 = 1 + x + x2 + x3 + · · · . (2) 1−x Because this series is a geometric series, we were able to prove that the series converges and converges to the function f (x) = 1/(1 − x). If we evaluate both sides of equation (1) at x = a, we get f (a) = a0 . . If we diﬀerentiate both sides of equation (1), we get f ′ (x) = a1 + 2a2 (x − a) + 3a3 (x − a)2 + · · · And if we evaluate (3) at x = a, we get f ′ (a) = a1 . . If you diﬀerentiate again and set x = a, you get f ′′ (a) = 2a2 , etc. In general, diﬀerentiating n times, setting x = a and solving for an , we get f (n) an = (4) n! and ∞ f (n) (a) f (x) = a0 + a1 (x − a) + a2 (x − a)2 + a3 (x − a)3 + · · · = (x − a)n . (5) n! n=0 This result is precisely what we predicted in our Motivation section. We computed the Taylor polynomial (in that section, of e3x ) and wondered whether we could replace the upper limit on the Taylor series summation by an inﬁnity. However, at the moment we only know that this is true when we know that the function has a power series expansion like equation (1). We make the following deﬁnitions. Deﬁnition 3.1 Let f be a function with derivatives of all orders on some interval containing a. Then the Taylor series of f at x = a is f ′′ (a) f ′′′ (a) f (n) (a) (x − a)n = f (a) + f ′ (a)(x − a) + (x − a)2 + (x − a)3 + · · · n! 2! 3! n=0 The Maclaurin series of f is f (n) (0) n f ′′ (0) 2 f ′′′ (0) 3 x = f (0) + f ′ (0)x + x + x + ··· n! 2! 3! n=0

∞ ∞

(3)

1 in Section 1.2 Compute the Taylor series of (a) f (x) = ln x about x = 1 and (b) f (x) = sin x about x = π/2. HW3. Hence. And of course. We proceed as follows. we can use that information to help write the Maclaurin series. series (6) converges for all x.1 Write the Maclaurin series of f (x) = sin x. We must be very clear. At this time we only know that the series in (6) is the Maclaurin series expansion of f (x) = sin x. We see that all of the even order derivatives at x = 0 will be zero. The functions that we care about are nicer so we get better results. We return to Example 1.3 Show that the Maclaurin series of the function f (x) = sin x. Example 3. series (6). The odd multiple derivatives will alternate between 1 and −1. It is also easy to see that based on the computation done above. Thus we see that the Maclaurin series of f (x) = sin x is a very nice series—it converges for all x. (2k + 1)! (6) We note also that the above series is really an easy generalization of the expression for T6 (x). Example 3.2 Determine for which values of x the Maclaurin series of f (x) = sin x is convergent. if we have already found Taylor polynomials of various orders for f (x) = sin x. bHW3. Example 3. It would be nice if the series converged to f (x) = sin x. converges to f (x) = sin x. We compute |an+1 | = |an | (−1)n+1 2n+3 (2n+3)! x (−1)n 2n+1 (2n+1)! x = |x|2n+3 (2n + 1)! |x|2 = →0 (2n + 3)! |x|2n+1 (2n + 3)(2n + 2) for all x.2 It is easy to see that the Maclaurin series of f is just the Taylor series of f at x = 0. We do not know where that series converges (if at all) or whether it converges to f (x) = sin x.1 Compute the Maclaurin series of the functions (a) f (x) = ex and (b) f (x) = cos x. In the text there is the example of the function f (x) = 2 e1/x when x = 0 where they claim that the Maclaurin series converges for all values of x but converges 0 when x = 0 to f (x) only at x = 0. the series given in (2) is the Maclaurin series of the function f (x) = 1/(1 − x). we can write the Maclaurin series of f (x) = sin x as 1 1 1 1 x − x3 + x5 − x7 + · · · = 1! 3! 5! 7! ∞ k=0 (−1)k 2k+1 x . we will apply the ratio test to determine where the series converges. As we did in the power series section. This is a fairly artiﬁcial example but it shows what we are up against. . It should be clear that it is relatively easy to write Taylor series expansions—since we already know how to write Taylor polynomials. −∞ < x < ∞. Hence. If you want to write the Maclaurin series of f (x) = sin x. as we did in Sections 1 and 2 we would generally make a table of derivatives that contains the derivatives of the function and the derivative at x = 0.

e. that Rn (x) converges to zero.1. or f (x) − Tn (x) = Rn (x) (7) where Tn (x) is the nth order Taylor polynomials and Rn (x) is the associated nth order error term. We .e. Thus if |Rn (x)| → 0. i. Recall that Rn (x) is given by Rn (x) = (−1)n In this example f (n+1) (t) = ± sin x ± cos x when n is even when n is odd 1 n! x (t − x)n f (n+1) (t) dt.3 The following paragraph is a very important paragraph. that we could write f (x) as f (x) = Tn (x) + Rn (x). It should be clear that the partial sums sn of the Maclaurin series are just the Taylor polynomials Tn (x).we must show that Tn (x) converges to f (x). In Section 1 we saw. we should be aware that a reasonably easy application of the Sandwich Theorem yields that Rn (x) → 0 if and only if |Rn (x)| → 0. ﬁnally. equations (1. to show that the Maclaurin series of the function f (x) = sin x converges to f (x) = sin x for some particular x. Hence. However.6). The convergence proof given above looks harder than it really is—mainly because a lot of explanation was given. However. we must show that the sequence of partial sums of the Maclaurin series converges to f (x) = sin x. hopefully to help you understand the proof. we can use Formula 6 from the Text (maybe Table 8. maybe page 625—the proof of Formula 6 they thought was diﬃcult enough so that it is relegated to Appendix 6) to see that this limit goes to zero. We must understand that to show that the Maclaurin series of the function f (x) = sin x converges to f (x) = sin x for some particular x. i. we see that |Rn (x)| = ≤ ≤ = (−1)n 1 n! x (t − x)n f (n+1) (t) dt 0 x 1 (t − x)n |f (n+1) (t)| dt n! 0 x 1 (t − x)n dt used the bound |f (n+1) (t)| ≤ 1 n! 0 1 |x|n+1 1 = |x|n+1 . And. 0 (8) so in any case. Read it again. We must keep the absolute value outside of the integral to allow for the case when x < 0. it is easy to see that |f (n+1) (t)| ≤ 1. And using the same analysis we used to develop the Taylor Inequality. Read it. that f (x) − Tn (x) converges to zero. For the Maclaurin series for the function f (x) = sin x proving that Rn (x) → 0 is not very diﬃcult. And then read it carefully.) It is not trivial to see that this term goes to zero as n approaches inﬁnity. n! n + 1 (n + 1)! (9) (Note that the step labeled (9) is using the property that you can take an absolute value inside of an integral. We will generally work with |Rn (x)|. f (x) = sin x is a very nice function.4)-(1. then Rn (x) → 0 (by the Sandwich Theorem) and Tn (x) → f (x) which shows that the Maclaurin series converges to f (x) = sin x.

It comes out of the integral because the integration is with respect to t. we see that the Taylor series of f (x) = ex at x = −1 converges for any x. We see that |Rn (x)| = ≤ ≤ = (−1)n 1 n! x −1 (t − x)n f (n+1) (t) dt x 1 (t − x)n |f (n+1) (t)| dt took the absolute value inside the integral n! −1 x 1 max{x. Example 3.1. page 625). Since Rn (x) → 0 as n → ∞. converges to f (x) = e−x .5 Determine for which values of x the Taylor series of f (x) = ex at x = −1 is convergent. not x.4 have to be able to show that the Taylor series of a function converges to the given function for something more diﬃcult than a sine or cosine function.−1} |x + 1|n+1 . As we did for Taylor polynomials we build a table as follows. e−1 + e−1 (x + 1) + e−1 (x + 1)2 + e−1 (x + 1)3 + · · · = 2 6 n! n=0 ∞ (10) Example 3.6 Show that the Taylor series of the function f (x) = e−x at x = −1. Hence. Table 8.3 (maybe Formula 6. Tn (x) and the Taylor series of f (x) = ex at x = −1 converges to f (x) = ex .4 Write the Taylor series of f (x) = ex at x = −1. Since x is ﬁxed. Consider the following examples.2 and use the Ratio Test. (n + 1)! This last term goes to zero as n goes to inﬁnity for the same reason that we got converges in Example 3.3. n f (n) (x) f (n) (−1) 0 ex e−1 x 1 e e−1 x 2 e e−1 x 3 e e−1 x 4 e e−1 x n e e−1 Then it is easy to see that the Taylor series of f (x) = ex at x = −1 can be written as e−1 1 1 (x + 1)n . We use the same approach as we did in Example 3. We should note that the bound we used for f (n+1) (t) = et would be ex if x ≥ −1. −1} to take care of the case when x < −1.−1} e (t − x)n dt n! −1 (11) emax{x. We proceed as we did in Example 3. Example 3. . We see that an+1 = an e−1 (n+1)! (x e−1 n! (x + 1)n+1 + 1)n = |x + 1| →0 n+1 as n → 0 for any x. series (10). We need the ”ugly” max{x. this will work.

Since this result is true for any interval (and it won’t always be). ∞)). d) that contains −1. d) |Rn (x)| = (−1)n 1 n! x (t − x)n 3n e3t dt ≤ −1 e3b 3n |x + 1|n+1 .3 and 3. (The Taylor series was computed in HW3. d). ”Discuss the convergence” means to determine where (for which values of x) the series converges and prove that the series converges to the given function (or show that it does not). b).1. and speciﬁcally the last description of the result of Example 3. If you return to your work.7 Write the Taylor series of f (x) = e3x at x = −1 and discuss the convergence of that series.5 Another way to express the results and the proof of Example 3.6 is to consider any x in an interval (c.3-3. Theorem 3. 1.) HW3. Example 3. We see that an+1 = an = 3 |x + 1| → 0 n+1 for all x. b).4 Discuss the convergence of the Taylor series of the function f (x) = sin x about x = π/2.6. Since this statement is true for any interval (a.1 Suppose that f has derivatives of all orders on the interval (c. 2 n! n=0 3n+1 e−3 n+1 (n+1)! (x + 1) 3n e−3 n n! (x + 1) ∞ (12) We apply the ratio test. Hence. Then in the analysis above we can use the bound eb for et (and take it out of the integral). Rn (x) → 0 and the Taylor series of f (x) = e3x at x = −1 converges to f (x) = e3x for all x ∈ (a. allows us to write the following theorem. d). the nth derivative is not bounded on any interval (a. d) and that there is M > 0 such that |f (n) (t)| ≤ M for k = 0.6 (old Formula 6 again). it is true for ℜ1 = (−∞. b) that contains −1. The result would then be that the Taylor series of f (x) = ex at x = −1 converges to to f (x) = ex on the interval (c. d) be some interval in the reals such that −1 ∈ (c. d). the end result is that the Taylor series of f (x) = ex at x = −1 converges to to f (x) = ex for any x (or on ℜ1 = (−∞. . (Both series were computed in HW3. then the Taylor series of f (x) at x = a converges to f (x) for any x ∈ (c.) Note: In homeworks such as 3. you will see that the nth derivative of f is f (n) (x) = 3n e3x . Using the fact that the nth derivative is given by f (n) derivative is given by f (n) (x) = 3n e3x . d).2 we considered the Taylor polynomial of f (x) = e3x at x = −1. (n + 1)! |Rn (x)| → 0 for the same reason we used in Examples 3. Since for x ∈ (c.7 we can still get convergence. we can write the Taylor series as e −3 + 3e −3 3n e−3 1 (x + 1) + 32 e−3 (x + 1)2 + · · · = (x + 1)n . ∞). The result of the above theorem sounds good but it really doesn’t give us all that we’d like. Let c. . HW3. . Hence.3 Discuss the convergence of the Maclaurin series of the functions (a) f (x) = ex and (b) f (x) = cos x. But as we see in Example 3. This last result. d). In HW2. hence. and t ∈ (c. .2. Then if a ∈ (c.4. Taylor series (12) converges for all x..

8 Find the Maclaurin series of the following functions and discuss their convergence. n! 3n n! n=0 n=0 ∞ ∞ x 3 for x gives (16) Again series (16) inherits its convergence from the Maclaurin series of f (x) = ex .1.) Substitution: Once we have a bunch of Maclaurin series.18). If we substitute 3x for x. i. (2k + 1)! (13) This series converges for all x. −∞ < 3x < ∞ which is the same as all x. (ref3.) (b) Discuss the convergence of the Maclaurin series expansion of f (x) = 1/(1 − x). the Taylor series of that functions converges to that function.1. series (14) will converge for x.3.e.6 Thus we see that Theorem 3. Consider the following. substitution can be used to help us ﬁnd more series. or −∞ < x < ∞. −∞ < x < ∞.19) converges for x. So series (ref3. (b): I HW3.e.1 to show it (even though they don’t have derivatives that are bounded on some iterval uniformly in n). −∞ < x < ∞. i.1).7. We get e3x = 3xn 3n xn = . (The series is given in (ref3. Example 3. −∞ < x < ∞. In this case prove the convergence using both the fact that it is a geometric series and use the approach introduced in Example 3. Substituting ex/3 = x/3n xn = . 3 (c): Proceeding as we did in part (b). HW3.7 shows us there are some very nice Taylor series of very nice functions that converge to the given function even though we can’t use Theorem 3. (This Taylor series was computed in HW3.1-3. (2k + 1)! (14) Series (14) will inherit of convergence of series (13).2. (a) f (x) = sin 3x (b) f (x) = ex/3 (c) f (x) = e3x (a): If we consider Example 3. we get ∞ sin 3x = k=0 (−1)k (3x)2k+1 = (2k + 1)! ∞ k=0 (−1)k 32k+1 2k+1 x .1 we found that ∞ xn ex = (15) n! n=0 and that the series converged for all x. for all x.1 tells us (if it could speak) that for certain very nice functions. −∞ < x < ∞. Example 3.5 (a) Discuss the convergence of the Taylor series expansion of f (x) = ln x about x = 1. we know that the Maclaurin series expansion of f (x) = sin x equals f (x) = sin x (converges to f (x) = sin x) and ∞ sin x = k=0 (−1)k 2k+1 x . we substitute 3x for x in series (15). n! n! n=0 n=0 ∞ ∞ (17) .

we can use the Maclaurin series of cos x.1 to obtain the convergence of the series on (c. to ﬁnd that the Taylor series of the function f (x) = (x + 1)2 ex at x = −1 is given by (x + 1)2 ex = (x + 1)2 e−1 e−1 (x + 1)n = (x + 1)n+2 . For the functions given in both parts (a) and (b). For example (multiplication). series (17) inherits the convergence from series (15) so series (17) converges to f (x) = e3x for all x. found a bound M so that |f (n) (x)| ≤ M for all x ∈ (c. Since the nth derivative of f (x) = e3x is f (n) (x) = 3n e3x . ∞ cos x = k=0 (−1)k 2k x (2k)! (18) to determine the Maclaurin series of x cos x by multiplying both the cos x and the series given in (ref3.7 could be used to prove the convergence of series (17). n! n! n=0 n=0 ∞ ∞ (20) We should realize that we can also use substitution and multiplication to ﬁnd certain Taylor series expansions—but they must be very special functions. HW3. 3 (23) to get the Taylor series expansion of f (x) = sin(x − 1) about x = 1. if we use the Taylor series expansion of f (x) = ex at x = −1.21) by x to get ∞ ∞ (−1)k 2k (−1)k 2k+1 x cos x = x x = x (19) (2k)! (2k)! k=0 k=0 Likewise we can compute the Maclaurin series of the function f (x) = x2 e3x using series (17) and get x2 e3x = x2 3n xn+2 3n xn = . d) and hence on all of ℜ. n! n! n=0 n=0 ∞ ∞ ∞ (21) We can substitute x − 1 for x in series (13) to see that sin(x − 1) = k=0 (−1)k (x − 1)2k+1 (2k + 1)! (22) Or we can substitute 3x for x in 1 n ) . (10). it is clear that it is impossible to ﬁnd a bound M that would bound the derivatives on any interval for all n. series (10) to get ∞ ∞ e−1 3n e−1 e3x = (3x + 1)n = (x + n! n! n=0 n=0 .” For example. Thus Theorem 3.1 was used to prove the convergence of series (15) which we used to prove the convergence of series (17). d) be any interval containing x = 0. It should be noted that the technique used in Example 3. d) and all n. and applied Theorem 3. Example 3.6 Compute the Maclaurin series of the following functions and discuss the convergence of the resulting series: (a) f (x) = 1/(1 − 2x).1 cannot be used directly to prove the convergence of series (17)—yet Theorem 3.7 Again. (b) f (x) = cos πx. we could have let (c.8(c) is sort of special. (c) f (x) = 1/(2 + 3x2 ) Multiplication: Another class of ”nice functions” of which we can easily compute the Maclaurin series are some ”nice products.

the last three examples are fairly contrived.e.8 and equations (19) and (20) show that substitution and multiplication are useful tools for ﬁnding some Maclaurin series.7 Compute the Maclaurin series expansions of the following functions: (a) f (x) = x2 /(1 − x).8 1 i. (b) f (x) = x2 /(x + x2 ). (c) f (x) = x2 sin x. the Taylor series of f (x) = e3x at x = 3 is given by the series (23). HW3. It should be clear that while the Maclaurin series found in Example 3. .

Are you sure?

This action might not be possible to undo. Are you sure you want to continue?

We've moved you to where you read on your other device.

Get the full title to continue

Get the full title to continue listening from where you left off, or restart the preview.

scribd